Hubungan konseling terhadap pengambilan keputusan kesertaan keluarga berencana dalam perspektif HAM di kota yogyakarta - Tri Wahyuning Puji Astuti; Trihoni Nalesty Dewi; Tjahjono Kuntjoro (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2016)
This research aimed to determine the relationship between the counceling given and the family planning decision in a prespective human right. This research method using Juridical sociology approach with qualitative research explanative. The results showed that the implementation of family planning counceling in human rights perspective has been conducted before the family planning service in community health centers (Puskesmas). The relevant stakeholders facilitated several program such as training for improving human resource competencies regarding with counseling and rights material. The midwives have given the family planning counceling with attention to human rights and reproductive rights after the training. The acceptor candidate, who has been given counceling, had felt better understanding to choose the contraception method and to decide using the family plannin. There was 60% patient took a decision in family planning.